Good Corporate Governance dalam Perspektif Hukum Pidana Internasional: Upaya Penanganan Pelanggaran HAM oleh Perusahaan Multinasional melalui Tinjauan Literatur - Zaenudin, Zaenudin; Fadilah, Putri Fatma; Putri, Rindi Dwi (SJEE (Scientific Journals of Economic Education), 2025)
This study explores the role of international criminal law in supporting the implementation of Good Corporate Governance (GCG) to prevent and address human rights violations by multinational corporations. Using a literature review approach, the study analyzes international legal principles such as the Rome Statute and the UN Guiding Principles on Business and Human Rights. The findings indicate that international criminal law significantly contributes to enhancing corporate accountability and transparency through the implementation of human rights due diligence principles. However, challenges such as cross-border jurisdiction and the lack of regulatory harmonization remain major obstacles to enforcing corporate responsibility. This study also highlights the importance of collaboration between international regulators and corporations to ensure ethical and sustainable business practices. In conclusion, the synergy between international criminal law and GCG can strengthen human rights protection in a global business context, with recommendations for developing more inclusive regulatory frameworks and further studies on its effectiveness across various industrial sectors.